Traffic Monitoring and Analysis 6th International Workshop, TMA 2014, London, UK, April 14, 2014. Proceedings - Dainotti, Alberto; Mahanti, Anirban; Uhlig, Steve (Springer eBooks, 2014)
This book constitutes the proceedings of the 6th International Workshop on Traffic Monitoring and Analysis, TMA 2014, held in London, UK, in April 2014. The thoroughly refereed 11 full papers presented in this volume were carefully reviewed and selected from 30 submissions. The contributions are organized in topical sections on tools and lessons learned from passive measurement, performance at the edge, and Web, content, and interdomain.